THE EFFECTIVENESS OF THE USE OF BOS FUNDS AND ITS IMPACT ON THE PERFORMANCE OF HIGH SCHOOL PRINCIPALS IN SI EMPAT NEMPU HILIR DISTRICT - Samosir, Herrison Yehuda; Lubis, Maksum Syahri; Batubara, Beby Masitho (Universitas Negeri Medan, 2024)
This study aims to analyze the effectiveness of the use of the School Operational Assistance Fund (BOS) and its impact on the performance of school principals at SMA Si Empat Nempu Hilir District. The research method used was a survey with a sample of 122 respondents, consisting of 1 principal, 23 teachers, and 98 students. Data was collected through a questionnaire that measured the effectiveness of the use of BOS Funds as well as the performance of school principals. The results of the descriptive analysis show that the effectiveness of the use of BOS funds is in the effective category with an average score of 4.03. Meanwhile, the performance of the principal was considered good with an average score of 4.13. A simple linear regression test revealed that the effectiveness of the use of BOS funds had a significant effect on the performance of school principals, with a regression coefficient of 0.45 (p < 0.05). These findings show that good management of BOS funds can improve the performance of school principals, which in turn has a positive impact on the quality of education in schools. This study suggests the need for improvements in the evaluation of the use of BOS funds to achieve more optimal effectiveness and support the improvement of school performance in the future.